Common bean response to cover crop straw and topdressing nitrogen fertilization - Pedrinho, Alexandre [UNESP]; Mariano, Eduardo [UNESP]; Merloti, Luis Fernando [UNESP]; Danielson, Rachel Elizabeth; de Sá, Marco Eustáquio [UNESP] (Southern Cross Publishing, 2018)
The use of cover crop mixtures (i.e., grass-legume), in association with N topdressing in common bean (Phaseolus vulgaris L.) has attracted interest due to the potential for increased seed yield and enhanced sustainability of the agroecosystem. This study evaluated cover crops (grass vs. grass-legume mixtures) and varied N fertilizer rates on crop parameters of common bean cultivated in a no-till system. A 5 × 4 factorial experiment tested pear millet (Pennisetum glaucum; PM), pear millet-jack bean (P. glaucum; Canavalia ensiformis; PM-JB), pear millet-pigeon pea (P. glaucum; Cajanus cajan; PM-PP), pear millet-sunn hemp (P. glaucum; Crotalaria juncea; PM-SH), and pear millet-velvet bean (P. glaucum; Mucuna pruriens; PM-VB) cover crop mixtures in a tropical system. After desiccation of the cover crops, common bean was seeded and then topdressed with three N rates (50, 100, and 150 kg N ha-1). A control (N-unfertilized) was also used. No differences related to dry biomass production and nutrient accumulation by the cover crops were detected, with the exception of S, with higher content in the PM than the PM-VB. The PM-JB mixture combined with N fertilizer addition increased the majority of the nutritional and yield parameters of common bean. For seed yield, application of 50 kg N ha-1 should be prioritized under PM-JB residues, while the input of 150 kg N ha-1 is recommended following PM-PP cultivation. Conversely, at 100 kg N ha-1 and without N addition, any cover crop treatment can be used.
Keywords: Cover crop mixtures; Legume; No-tillage; Pear millet; Phaseolus vulgaris L.; Topdress nitrogen